Patent foramen ovale occlusion with the Cocoon PFO Occluder. The PROS-IT collaborative project - Testa, Luca; Popolo Rubbio, Antonio; Squillace, Mattia; Albano, Flavio; Cesario, Vincenzo; Casenghi, Matteo; Tarantini, Giuseppe; Pagnotta, Paolo; Ielasi, Alfonso; Popusoi, Grigore; Paloscia, Leonardo; Durante, Alessandro; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The Cocoon patent foramen ovale (PFO) Occluder is a new generation nitinol alloy double-disk device coated with nanoplatinum, likely useful in patients with nickel hypersensitivity. Early results and mid-term outcomes of this device in percutaneous PFO closure are missing. Aims To assess the preliminary efficacy and safety profile of PFO closure with Cocoon device in an Italian multi-center registry. Methods This is a prospective registry of 189 consecutive adult patients treated with the Cocoon PFO Occluder at 15 Italian centers from May 2017 till May 2020. Patients were followed up for 2 years. Results Closure of the PFO with Cocoon Occluder was carried out successfully in all patients, with complete closure without residual shunt in 94.7% of the patients and minimal shunt in 5.3%. Except from a case of paroxysmal supraventricular tachycardia and a major vascular bleeding, no procedural and in-hospital device-related complications occurred. No patient developed cardiac erosions, allergic reactions to nickel, or any other major complications during the follow-up. During the follow-up period, 2 cases of new-onset atrial fibrillation occurred within thirty-day. Conclusions Percutaneous closure of PFO with Cocoon Occluder provided satisfactory procedural and mid-term clinical follow-up results in a real-world registry.